MODIFICATION AND PERFORMANCE EVALUATION OF AN IMPORTED THREE-ROW ANIMAL-DRAWN MAIZE PLANTER FOR PLANTING SOYBEANS - Alhassan, S.; Saleh, Aminu; Mohammed, U. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Increase in demand of functional and affordable planters and the inability of the peasant farmers in Nigeria to purchase imported planters stressed the need for development of a locally produced planters that could address the challenges encountered in grain planting. A three row imported animal-drawn maize planter was modified having identified its deficiencies. The modified planter consists of hopper, seed metering device, delivery tube, furrow opener, covering device, pressing wheel, frame, handle and traction wheel. It was evaluated in the laboratory and field using maize and Soybean as test crops. Parameters determined are planting speed, seedling emergence, plant to plant spacing, effective field capacity, germination count, planting efficiency, seed delivery rate, number of seeds per hole and percent seed damage. A combination of three planting speeds (2, 1.1 and 0.8m/s) and three seed weights (2.9, 2.2 and 1.1kg) were used for the performance evaluation. Results obtained were analyzed in a Completely Randomized Block Design. It showed that seed delivery rate was 24.8kg/ha and effective field capacity was 0.12ha/ha while the highest germination count of 83% was obtained at 0.8m/s planting speed and 2.9kg seed weight. The best of planting efficiency of 86.4% was obtained at 1.1m/s planting speed and 2.9kg seed weight. Plant to plant distance of 26.4cm was obtained at 2m/s planting speed and 2.2kg seed weight. One seed per hill was obtained at the all combinations. The modified planter has proved to be suitable for eliminating the limitations associated with the imported planter.